Juvenile pityriasis rubra pilaris with low C3 in a 5-year-old child. - Alqarni, A.A.; Alsohaimi, A.A.; Alzahrani, A.S.; Alghamdi, E.S. (European Journal of Pediatric Dermatology, 2014)
Pityriasis rubra pilaris (PRP) is a rare papular and quamous disorder of unknown etiology characterized by reddish orange plaques with pityriasiform scaling, follicular keratosis, palmoplantar keratoderma, and occasionally erythroderma. We hereby report a 5-year-old child with juvenile circumscribed PRP and low C3.